2007
DOI: 10.1111/j.1600-6143.2006.01720.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transduction of an Active Mutant of Akt Exerts Cytoprotection and Reduces Graft Injury After Liver Transplantation

Abstract: Akt is expected to be an effective target for the treatment of ischemia-reperfusion injury (I/R) due to its anti-apoptotic properties and its ability to activate the endothelial nitric oxide synthase (eNOS) enzyme. Therefore, this study was aimed to determine the efficacy of an active mutant of Akt (myr-Akt) to decrease I/R injury in a model of orthotopic liver transplantation in pigs. In addition, we analyzed the contribution of nitric oxide in the Akt-mediated effects by using an eNOS mutant (S1179DeNOS) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 46 publications
(50 reference statements)
2
16
0
Order By: Relevance
“…In contrast, the old rats subjected to hepatic ischemia showed sustained caspase-3 activation and delayed Akt activation, resulting in prolonged apoptosis. It was found in recent studies that adenoviral gene transfer of the active mutant of Akt exerted anti-apoptotic effects against hepatic I/R injury, which supports our interpretation of our results [19,21]. In addition, the suppression of Akt activity by phosphatidylinositol 3-kinase (PI3K) inhibitor contributed to apoptotic damage and liver injury in mice after TNF-a administration [20], suggesting that Akt plays a crucial role in cell survival by inhibiting apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast, the old rats subjected to hepatic ischemia showed sustained caspase-3 activation and delayed Akt activation, resulting in prolonged apoptosis. It was found in recent studies that adenoviral gene transfer of the active mutant of Akt exerted anti-apoptotic effects against hepatic I/R injury, which supports our interpretation of our results [19,21]. In addition, the suppression of Akt activity by phosphatidylinositol 3-kinase (PI3K) inhibitor contributed to apoptotic damage and liver injury in mice after TNF-a administration [20], suggesting that Akt plays a crucial role in cell survival by inhibiting apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the suppression of Akt activity by phosphatidylinositol 3-kinase (PI3K) inhibitor contributed to apoptotic damage and liver injury in mice after TNF-a administration [20], suggesting that Akt plays a crucial role in cell survival by inhibiting apoptosis. The PI3K/ Akt pathway is a 'survival signaling pathway', the downstream targets of which are involved in antiapoptosis, anti-oxidative defense, and protein synthesis [18][19][20][21]. As for the effect of aging on the PI3K/Akt pathway, our results suggested that delayed Akt activation; i.e., delayed protection against apoptosis, may affect the recovery from liver injury after hepatectomy in old rats that have been subjected to ischemic insult.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Since the mid 1990s, our group has used a simplified technique to perform hundreds of liver transplants in pigs with consistent success [15][16][17][18][19][20]. The purpose of this work is to communicate, in detail, how to reproduce this technically straightforward model, from the induction of anesthesia to the postoperative follow-up.…”
Section: Introductionmentioning
confidence: 98%